2019
DOI: 10.24853/elif.1.1.55-64
|View full text |Cite
|
Sign up to set email alerts
|

Using Graphic Organizer to Improve Students’ Speaking skill

Abstract: The purpose of this study was to determine whether Graphic Organizer has a significant effect on students' ability to speak. This study used the VIII.F students of Al-Azhar 12 Junior High School Rawamangun as the research sample. This class consists of 22 students. To choose the sample, the writer used a simple random sampling technique. From the population. The method used in this study was quantitative and the design used was a pre-experimental study with the technique of one group pre and post-test design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Rizqningsih and Hadi (2019) mentioned some components to have in order to speak English fluently and accurately, these components namely: 1) grammar; 2) Vocabulary; 3) Pronunciation; 4) Fluency; and 5) Comprehension. Saindra and Mutiarani (2018) stated that among the four language skills, speaking skill is the most crucial skill to have since without having the skill people cannot understand others' thoughts and ideas, because they cannot express it clearly. Speaking materials in English textbook have lots of advantages.…”
Section: The Language Skills In English Textbooksmentioning
confidence: 99%
“…Rizqningsih and Hadi (2019) mentioned some components to have in order to speak English fluently and accurately, these components namely: 1) grammar; 2) Vocabulary; 3) Pronunciation; 4) Fluency; and 5) Comprehension. Saindra and Mutiarani (2018) stated that among the four language skills, speaking skill is the most crucial skill to have since without having the skill people cannot understand others' thoughts and ideas, because they cannot express it clearly. Speaking materials in English textbook have lots of advantages.…”
Section: The Language Skills In English Textbooksmentioning
confidence: 99%
“…Some of the previous studies have used graphic organizers in their research. Ilter (2016), Al-Hinnawi (2012), Saindra &Mutiarani (2019), andZaini, et. al (2010) have shown that learning with graphic organizers can improve students' understanding, performance, and motivation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kansızoğlu (2017) found that academic success, including listening, reading, writing, grammar, and vocabulary, could be better enhanced with the use of graphic organizers compared to traditional techniques. Parrish (2018) used YouTube clips as a source for authentic listening clips and a flow chart to improve students' critical reading skills, while Saindra and Mutiarani (2018) used a graphic organizer to improve students' speaking skills in junior high school, both with success. Likewise, Sathongeay and Prasansaph (2019) found that critical reading skills of undergraduate students were significantly higher with the use of graphic organizers.…”
Section: Previous Studies Related To Visual Literacy With 21st Centur...mentioning
confidence: 99%